Enhancing MSME Economy through Social Media in the Covid-19 Pandemic Era - Umah, Yuli Choirul; Lestari, Veronika Nugraheni Sri; Lestari, Lilla Puji (Bisma : Bimbingan Swadaya Masyarakat, 2023)
The purpose of this research is to improve the economy of MSMEs through social media in Sambiroto village. This research is conducted by the ABCD (Assets Based Community Development) method with dimulai from assets and power owned by the community, assets to develop the potential / opportunities that exist. assets organized and mobilized, and finally mandiri and sustainability. The results of the research using the ABCD approach method, para business people of Sambiroto village MSMEs finally began to know social media as a marketing tool and began to be interested in social media for the marketing of MSME products. With Social Media, Sambiroto village MSME products are better known by the wider community so that sales turnover increases